Insights Into the Electronic Properties of PbBi Atomic Layers on Ge(111) and Si(111) Surfaces - Mihalyuk, A. N.; Vekovshinin, Y. E.; Bondarenko, L. V.; Tupchaya, A. Y.; Utas, T. V.; Gruznev, D. V.; Eremeev, S. V.; Zotov, A. V.; Saranin, A. A. (Frontiers in Materials, 2022)
Co-adsorption of Pb and Bi onto Si(111) and Ge(111) surfaces has been found to result in formation of atomic-layer PbBi compounds having similar structures. These are two co-existing crystalline PbBi phases with $2\sqrt{3}$$×$$2\sqrt{3}$ and 2$×$2 periodicities. Using density functional theory calculations, we found that these two phases present insulating and highly anisotropic metallic systems, respectively. However, electronic structure of the metallic 2$×$2-PbBi phase on Ge(111) appears qualitatively different from that on the Si(111). We investigated electronic properties of the PbBi compound considering the effects induced by the different supporting substrates, namely Si(111) and Ge(111). As a part of comparative study, we made the chemical-bonding analysis and examined a free-standing PbBi layer inspecting the dependence of its spectral characteristics on the compressive/tensile strain. We believe that the present findings will play an important role in the development of new electronic devices fabricated in the ultimate two-dimensional limit.